ANALISIS KINERJA SIMPANG STAGGER PADA JL. SULTAN ABDURRAHMAN – JL. JOHAN IDRUS – JL. PUTRI CANDRAMIDI KOTA PONTIANAK - Budiman, Febri; Erwan, Komala; ., Said (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2016)
The rapid growth of vehicles and the limited capacity of urban roads lead to problems in the field of transport. Particularly in the area of ​​the intersection, which is often congested and long lines. Setting the intersection with the traffic light control to be planned in accordance with the amount of traffic passing through the intersection, so that traffic can be served well and generate optimum performance intersection. The purpose of this study to determine the amount of traffic flow and the level of performance stagger signalized intersection Jl. Sultan Abdurrahman-Jl. Johan Idrus-Jl. Putri Candramidi Pontianak, and find alternative solutions to problems that can be applied to optimize the performance of the intersection. The data used in this study consisted of primary data include: geometry conditions, the environment, traffic and signaling, as well as secondary data comprising: a map of the location of research and population. Performance optimization on the existing conditions using the Indonesian Highway Capacity Manual (MKJI) 1997, www.harianregional.com with performance parameters, including capacity (C), the degree of saturation (DS), delay (D), and the long lines (QL). Based on the analysis of existing analysis obtained intersection signalized intersection performance stagger Jl. Sultan Abdurrahman-Jl. Johan Idrus-Jl. Putri Candramidi Pontianak City has not comply of manual MKJI 1997. It can be seen from the value of capacity (C), degree of saturation (DS), delay (D), long lines(QL), respectively (East: 1505 smp/hours; 0876 ; 45.56 det/smp ; 111.13 m), (West: 1019 smp/hour ; 0.957; 71.23 det/smp; 84.99 m), (South; 1186 smp/hour ; 0.930 ; 44.68 det/smp ; 70.51 m) , (North: 2195 smp/hour; 0431; 9:00 det/smp; - m). Based on the results of improvement alternative that provides the best value alternative form of mounting three wide median and the addition of closers. Alternative 3 can improve the performance of the intersection, the increase can be seen from the value of capacity (C), degree of saturation (DS), delay (D), long lines (QL), respectively (East: 1407 smp/hour; 0714 ; 41.92 det/smp; 42.44 m), (West: 1274 smp/hour; 0766; 41.41 det / smp; 50.32 m), (South: 1186 smp/hour ; 0.477; 40.22 det/smp; 36.72 m), (North : 2195 smp/hour; 0431; 9:00 det/smp; - m), an alternative overall has comply of MKJI 1997, then these alternatives may be applied in a stagger signalized intersection of Jl. Sultan Abdurrahman-Jl. Johan Idrus-Jl. Putri Candramidi Pontianak. Keywords :existing , alternative, degree of saturation, stagger